20.7k views
2 votes
Given y²+5y-6= (y+p) (y+q), find the values of p and q. ​

2 Answers

3 votes

Answer:

p = 6, q = - 1 , or p = - 1, q = 6

Explanation:

Factorise the quadratic expression on the left side

y² + 5y - 6

Consider the factors of the constant term (- 6) which sum to give the coefficient of the y- term (+ 5)

The factors are + 6 and - 1 , since

6 × - 1 = - 6 and 6 - 1 = + 5 , then

y² + 5y - 6

= (y + 6)(y - 1) = (y - 1)(y + 6)

Compare to (y + p)(y + q) , then

p = 6, q = - 1 or p = - 1, q = 6

User Thom Ives
by
4.2k points
2 votes

Answer:

(y+6)(y-1)

Explanation:

literally factorising.

y^2 x -6 = -6y^2

u need two numbers that multiply to make -6 and add them together to make +5 which is +6 and -1.

User Rjonnal
by
5.0k points